Arduino Uno-Based Early Fire Detection System Using MQ-2 Flame Sensor and Gas Sensor - Suci Rahmadani Haza Sitorus; Cyntia Natasya Panjaitan; Fanisha Silva Zulham (Smart Education, 2026)
Abstract: Fire is one of the disasters that frequently occurs and can cause material losses and casualties. Therefore, an early fire detection system is required to provide fast and accurate warnings. This study aims to design and develop an early fire detection system based on Arduino Uno using a flame sensor to detect fire and an MQ-2 gas sensor to detect flammable gases. The research method applied is a design and development approach, including hardware design, software programming, system assembly, and testing. Arduino Uno functions as the main controller that processes data from both sensors and activates a buzzer and LED as warning indicators when fire is detected or when gas concentration exceeds a predetermined threshold. The test results show that the system can automatically respond to the presence of fire and gas with relatively fast response time. This system can be used as a simple and effective solution for early fire prevention. Keyword: arduino uno; alarm system; fire detection; flame sensor; mq-2 gas censor. Abstrak : Kebakaran adalah salah satu bencana yang sering terjadi dan dapat menyebabkan kerugian material serta korban jiwa. Oleh karena itu, diperlukan sistem pendeteksi kebakaran dini yang mampu memberikan peringatan dengan cepat dan akurat. Penelitian ini bertujuan untuk merancang dan mengembangkan sistem deteksi kebakaran dini berbasis arduino Uno dengan memanfaarkan sensor api untuk mendeteksi api dan sensor gas MQ-2 untuk mendeteksi gas mudah terbakar. Metode penelitian yang digunakan adalah pendekatan perancangan dan pengembangan, meliputi desain perangkat keras, pemrograman perangkat lunak perakitan sistem dan pengujian. Hasil pengujian menunjukkan bahwa sistem dapat merespons keberadaan api dan gas secara otomatis dengan waktu respons yang relatif cepat. Sistem ini dapat dijadikan sebagai solusi yang sederhana dan efektif dalam upaya pencegahan kebakaran sejak dini. Keywords :? arduino uno; deteksi kebakaran; sensor api; sensor gas mq-2; sistem alarm.